Fostering Specialised Higher Nursing Education in India: Identifying Challenges and Crafting Solutions - Suresh K Sharma; Lily Podder (Journal of Medical Evidence)
As healthcare systems worldwide evolve to meet the increasing complexities of patient care, specialised higher nursing education has emerged as a pivotal component in enhancing the quality of healthcare delivery. In India, nurses constitute approximately 30.5% of the healthcare workforce; however, the nation faces significant challenges in developing a competent specialised nursing cadre. This article provides a comprehensive review of the obstacles in preparing specialised nurses, the challenges of retaining them and proposed strategies to overcome these issues. A systematic search of multiple electronic databases for studies published between 2013 and 2023 identified 28 relevant studies. Key obstacles in preparing specialised nurses were identified and categorised into educational barriers, institutional challenges and policy and regulatory issues. Retaining specialised nurses poses equal challenges, primarily due to job dissatisfaction, inadequate compensation, limited career advancement opportunities and the impact of international migration. Proposed solutions include modernising nursing curricula, establishing clear career pathways, enhancing work environments and reforming policies to improve retention. By addressing these challenges and implementing strategic recommendations, this review aims to contribute to the development of a more capable and specialised nursing workforce, ultimately enhancing healthcare delivery and outcomes in India.